PENGARUH TRANSPARANSI, TINGKAT MARGIN, DAN KEPATUHAN SYARIAH TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN PEMBIAYAAN MURABAHAH DI BMT BINA IHSANUL FIKRI (BIF) CABANG PARANGTRITIS DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERASI - SEPTIANA, DHETI (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
This research was conducted in order to gain an understanding on the effects of transparency, margin rate, and sharia conformity on customers’ decision to take Murabaha financing in BMT BIF Parangtritis, using religiousness as a moderating variable. This is a quantitative research and the data was gathered through questionnaires given to customers who took Murabaha financing in BMT BIF Parangtritis. Data sampling used purposive sampling technique from a pool of 87 respondents. The data was then analyzed using Moderated Regression Analysis (MRA). The results showed that transparency, margin rate, and sharia conformity affected customers’ decision to take Murabaha financing in BMT BIF Parangtritis. This showed that, the more transparent, the better the margin rate, and the higher sharia conformity level affected customers’ decision to take Murabaha financing in BMT BIF. The effects of transparency on customers’ decision to take on Murabaha financing was not moderated by religiousness. However, as a variable, religiousness moderated the effects of margin rate and sharia conformity on customers’ decision to take on Murabaha financing. From this, it could be concluded that customers’ religiousness level is not related to BMT’s transparency policy, therefore, not affecting their decision on taking Murabaha financing. However, higher religiousness levels did mean that the customers will pay more attention on the margin rate and sharia conformity of BMT BIF Parangtritis, thus affecting their decision on whether to take Murabaha financing or not.